Das experiências sensoriais aos conhecimentos matemáticos: uma análise das práticas associadas ao ensino e aprendizagem de alunos cegos e com visão subnormal numa escola inclusiva - Fernandes, Solange Hassan Ahmad Ali (2008)
This thesis examines issues concerning the relationship body cognition in a scenario composed of visually impaired students, working with the sighted, with mathematical tasks and with material and semiotic tools. It aims to analyse the teaching and learning processes of students included within regular classroom when the object of study is mathematics, particularly geometrical objects. The study was divided into two moments. The first concentrated on constructing an understanding of the school mathematics developed in the school attended by our subjects and the systems of assessments they were expected to participate in. In a second moment, the study took a more experimental turn, with the introduction of material and semiotic tools into learning situations. Analysis centred on the identification of how these tools could be used to constitute new practices associated with learning mathematical knowledge and explored the importance of that which is perceived by the senses in the production of this knowledge. Theoretical support was drawn from the work of contemporary researchers who adopt perspectives rooted in the vygotskian tradition. Specifically, analyses were informed by constructs related to the appropriation of the mathematical voice (Renshaw, 1996), the cognitive and communicate potential of gestures (McNeill, 1992) and the process of objectification of knowledge (Radford, 2004; 2004a). The results indicate, on the one hand, that the current practices associated with school mathematics do not always enable the active participation of visually impaired students while, one the other, suggestion a possible route by which to create a more inclusive mathematics education. This route involves an approach which attends to the role of various instruments of mediation (material and semiotic) and activities based on explorations of and dialogues about mathematical concepts in forms fine-tuned to allow the learners to capitalise on their whole perceptive field